The Design of Ecological Momentary Assessment Technologies. Issue 3 (27th August 2020) - Doherty, Kevin; Balaskas, Andreas; Doherty, Gavin
Abstract: Ecological Momentary Assessment (EMA) methods and technologies, designed to support the self-report of experience in the moment of daily life, have long been considered poised to revolutionize human-centred research, the practice of design and mental healthcare. The history of EMA is inextricably linked to technology, and mobile devices embody many of the characteristics required to support these methods. However, significant barriers to the design and adoption of these systems remain, including challenges of user engagement, reporting burden, data validity and honest disclosure. While prior research has examined the feasibility of a variety of EMA systems, few reviews have attended to their design. Through inter-disciplinary narrative literature review ( n = 342), this paper presents a characterization of the EMA technology design space, drawing upon a diverse set of literatures, contexts, applications and demographic groups. This paper describes the options and strategies available to the EMA systems designer, with an eye towards supporting the design and deployment of EMA technologies for research and clinical practice.